2011
DOI: 10.2527/jas.2010-3642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing Saccharomyces cerevisiae fermentation product in sow diets on performance of sows and nursing piglets1,2

Abstract: Forty-two sows were used to determine the effects of adding a Saccharomyces cerevisiae fermentation product (SCFP) to the gestation and lactation diets on the performance of sows and their progeny. At 5 d before breeding, sows were allotted to 2 dietary treatments representing 1) sows fed a diet with 12.0 g of fermentation product/d through gestation and 15.0 g of fermentation product/d through lactation (SCFP treatment, n=22), and 2) sows fed a diet with equal amounts of a mixture of corn and soybean meal ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 32 publications
7
77
2
3
Order By: Relevance
“…Supplementing with MRF has previously demonstrated benefits by promoting the proper function of the gastrointestinal tract and indirectly impelling good health and growth (van der PeetSchwering et al, 2007;Shen et al, 2011;Zhao et al, 2012). Our study is in agreement with previous results that reported MRF supplementation increased levels of IgG in sow colostrum, which may enhance piglet performance by improving immunocompetence (Jurgens et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supplementing with MRF has previously demonstrated benefits by promoting the proper function of the gastrointestinal tract and indirectly impelling good health and growth (van der PeetSchwering et al, 2007;Shen et al, 2011;Zhao et al, 2012). Our study is in agreement with previous results that reported MRF supplementation increased levels of IgG in sow colostrum, which may enhance piglet performance by improving immunocompetence (Jurgens et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Low level antibiotics were historically used to improve performance; however, probiotics and prebiotics have gained considerable attention as performance-enhancing alternatives. Alternatives to antibiotic growth promoters include supplemental yeast and yeast derived products that are beneficial to animal health, growth and performance (van der Peet-Schwering et al, 2007;Shen et al, 2011;Zhao et al, 2012). Mannan oligosaccharide, a family of yeast cell wall containing a mannan-rich fraction (MRF) derivatives, have gained attention for their value and role in immune modulation in swine species (Nochta et al, 2009;Czech et al, 2010;Che et al, 2011;Che et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation metabolites of XPC includes yeast cell wall fragments such as beta-glucans and mannan-oligosaccharides, yeast cell residues, and post-fermented growth medium residues (Shen et al, 2011). Based on previous studies, the assay utilized a 24 h adaptation period for each sample containing cecal contents and poultry feed (Donalson et al, 2007; Rubinelli et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The inadequacy or poor quality of dietary protein can increase serum concentration of urea (Shen et al, 2011). Serum urea nitrogen level was significantly higher in piglets fed control diet than in those fed SDPP diet (+119%, P<0.05), SDPP plus YP diet (+98%, P<0.05) and YP diet (+82%, P<0.05) ( Table 5).…”
Section: Page 165]mentioning
confidence: 99%